Preparation and characterization of expanded graphite polymer composite films for thermoelectric applications. Issue 12 (12th November 2013) - Piao, Mingxing; Kim, Gyutae; Kennedy, Gary P.; Roth, Siegmar; Dettlaff‐Weglikowska, Urszula
<x xml:space="preserve">Abstract</x> This report demonstrates application of expanded graphite (ExG) for thermoelectric energy conversion, where it serves as a filler for both p‐ and n‐type organic materials. Thin ExG composite films showing improved thermoelectric properties were prepared. In particular, composites with intrinsically conducting polymer poly(3, 4‐ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) yielding high electrical conductivity (up to 104 S m−1) and enhanced thermopower (Seebeck coefficient) provided promising p‐type material. Chemical doping experiments performed on ExG dispersed in polyvinyl alcohol (PVA) revealed that the exfoliated graphitic sheets can be efficiently n‐doped with polyethyleneimine (PEI). As a result, n‐type ExG/PVA/PEI composite thin films showing improved n‐type characteristics with thermopower values as high as −25.3 µV K−1 were prepared. With a 25 wt% ratio of PEI to ExG, the electrical conductivity was measured to be ∼103 S m−1, which is remarkably high for n‐type polymer composites. Strips of composite films containing 50 wt% of ExG in PEDOT:PSS were used as p‐type components, and composite films containing 20 wt% of ExG in PVA doped with PEI were used as n‐type components in thermoelectric modules to demonstrate thermoelectric voltage with one, two, and three p‐n couples connected in series. The testing modules produced an output voltage of ∼4 mV at a temperature gradient of 50 K. The module generated 1.7 nW power, when a load resistance matched the internal module resistance of 1 kΩ. Our results show that chemical functionalization of ExG in thin composite films resulted in more effective thermoelectric properties.